Prepare : Workbook Level 3 - Treloar, Frances ([Cambridge] Cambridge University Press, 2015)
Level 3 2nd edition book with in-depth topics for the revised 2020 A2 Key for School exam. The book provides additional reading, writing, and listening practice for the language covered in the PREPARE Level 3 Student Book units, while strengthening vocabulary. A special accompanying audio is available online for download via an access code in the Workbook. Student Books and Online Workbooks are also available, separately.
Keywords: Cơ bản